Causal Attribution in Academic Achievement Among Malay and Chinese Engineering Undergraduates in Universiti Putra Malaysia - Ong, Zen Kai (2006)
The purpose of this study was to examine causal attribution in the academic achievement of engineering undergraduates in Universiti Putra Malaysia. This study aimed to investigate and compare how Malay and Chinese students perceive causes for various success and failure situations, based on Weiner’s (1979) threedimensional taxonomy in categorizing causes. The dimensions are locus of causality, stability and controllability (further divided into personal and external controllability). A total of 146 second-year engineering students were selected using stratified sampling method. The instrument used in this study was the Revised Causal Dimension Scale (CDSII) designed by McAuley et al. (1992). Questionnaires were constructed using simulational technique, in which short stories in various situations of academic achievements were presented. Respondents were asked to read and identify intensively with the acting persons in the stories. Then, they were asked to explain causes for the result in that story. In this study, Malay students scored remarkably lower than Chinese students in terms of average score in CGPA (2.79 for Malays compared with 3.43 for Chinese). Despite evidencing on an average lower achievement than their Chinese counterparts, t-tests indicated that Malay subjects rated higher in locus (p < .01) and personal controllability (p < .01) dimensions while facing success situations. Correlation tests in success situations were consistent with the findings above, in which CGPA demonstrated negative relationships with both locus (p < .05) and personal controllability (p < .01) dimensions. This contradiction of low achievement versus high level in locus and controllability were further analyzed using subjective attributions provided by the respondents. Some implications for education were discussed based on culture as well as current social conditions in Malaysia. In general, Malay students believed that their effort will be rewarded, and make more internal and controllable attributions when faced with success in academic achievements. Chinese students also identified with consistent effort. However, unlike their Malay counterparts, Chinese students relatively disregarded the role of inconsistent effort in their achievement, thus made less internal and controllable attributions.